Growth Variation in Progenies of 50 ’plus’ Trees of Acacia nilotica (L.) Willd Ex. Del. Ssp. Indica (Benth.) Brenan of Central India - Arya, S.; Toky, O. P. (Indian Forester, 2006)
Acacia nilotica ssp. Indica, an important agroforestry tree occurs extensively on farmlands throughout semi-arid India. The seeds of 50 ’plus’ trees were collected from 5 states of Central India (21Â°14’ N to 29Â°59’ N lat., 72Â°38’ E to 85Â°20’ E long., 55 m to 655 m alt.), and studies on seed germination in polybags and growth in nursery beds and in field were carried out at the campus of Haryana Agricultural University, Hisar located in North-western India (29Â°10 N’ lat., 75Â°46’ E long., 215 m alt.). The seed weight of 50 plus trees ranged from 12.1 g to 21.5 g/100 seeds and seed germination from 27 to 86 per cent. Weight of the seed was significantly and positively correlated with longitude (r = 0.525, p<0.01), altitude (r = 0.431, p<0.01) and rainfall (r =0.497, p<0.01). The correlation with latitude was however, insignificant. The growth of 18 months old plants in the nursery varied significantly (P<0.05) among 10 mother plants of each state and also between states. The height of the plants ranged from 1.4 m of GJ-4 to 3.1 m of BH-4, the collar diameter from 11 mm of GH-4 to 19 mm of HR-7 and the dry weight of plant from 465 g/plant of GJ-4 to 1009 g/plant of BH-4. Two seed sources of Haryana i.e. HR-5 and HR- 6 showed exceptionally superior growth in all its 10 progenies. Similar trends were observed for plants growth in the field. The wide variability in A. nilotica ssp. indica is of great significance in selection of better genotypes, and further establishment of seed orchard.